IMPLEMENTASI MOTIVASI KERJA DALAM MENINGKATKAN PRODUKTIVITAS GURU MUATAN LOKAL - Hendri; Sesmiarni, Zulfani (Program Studi Magister Pendidikan Agama Islam, 2024)
This study aims to determine the motivation of teacher performance in increasing productivity in local content teachers in schools. Motivation is an encouragement that helps in achieving goals. In doing work, especially as a teacher, of course, requires motivation for himself to remain productive in doing work. The principal plays a very important role in helping to manage, create a comfortable and conducive environment at school. This research uses a descriptive qualitative approach. The data source was obtained from the principal and teachers. The procedures used in data collection are observation, interview, and documentation. The data analysis used the Miles and Huberman model which consists of data reduction, data presentation, and conclusions. Based on the results of research and discussion regarding the implementation of work motivation in improving the productivity of mulok teachers, it can be concluded as follows: (1) the work motivation of mulok teachers in schools can be seen from two motives, namely intrinsic and extrinsic motivation. (2) The principal is very instrumental in increasing teacher motivation, with the form of attention, praise and appreciation to each teacher, training, guidance. In general, it is known that the level of teacher work motivation is very high. (3) The impact of the work motivation of mulok teachers at school can be seen in two aspects, namely in terms of process and in terms of results. (4) Supporting factors that can improve teacher performance from internal and external elements, facilities and infrastructure, curriculum and methods, environment, teachers, and students. Abstrak Penelitian ini bertujuan untuk mengetahui motivasi kinerja guru dalam peningkatan produktivitas pada guru muatan lokal di sekolah. Motivasi merupakan dorongan yang membantu dalam tercapainya tujuan. Dalam melakukan pekerjaan khususnya sebagai seorang guru tentu membutuhkan motivasi bagi dirinya agar tetap produktif dalam melakukan pekerjaan. Kepala sekolah sangat berperan penting dalam membantu memanage, menciptakan lingkungan yang nyaman dan kondusif di sekolah. Penelitian ini menggunakan pendekatan kualitatif deskriptif Sumber data diperoleh dari kepala sekolah dan guru. Prosedur yang digunakan dalam pengumpulan data adalah observasi, wawancara, dan dokumentasi. Adapun analisis data menggunakan model Miles dan Huberman yang terdiri dari reduksi data, penyajian data, dan kesimpulan. Berdasarkan hasil penelitian dan pembahasan mengenai implementasi motivasi kerja dalam meningkatkan produktivitas guru mulok, maka dapat disimpulkan sebagai berikut: (1) motivasi kerja guru mulok di sekolah dapat dilihat dari dua motif yaitu motivasi intrinsik dan ekstrinsik. (2) Kepala sekolah sangat berperan dalam peningkatan motivasi guru, dengan bentuk perhatian, pujian dan penghargaan kepada setiap guru, pelatihan, bimbingan. Secara umum diketahui bahwa tingkat motivasi kerja guru sudah sangat tinggi. (3) Dampak dari adanya motivasi kerja guru mulok di sekolah dapat dilihat dari dua segi, yaitu dari segi proses dan segi hasil. (4) Faktor pendukung yang dapat meningkatkan kinerja guru dari unsur internal dan eksternal, sarana dan prasarana, kurikulum dan metode, lingkungan, guru, dan peserta didik.